Protective and Risk Parenting Styles for Internet and Online Gambling Addiction - Cristina Serna; Joan García-Perales; Isabel Martínez (Human Behavior and Emerging Technologies)
This study analyzes the relationship of the four parenting styles, authoritative, authoritarian, indulgent, and neglectful, with Internet addiction and online gambling addiction. Study sample was 512 adolescents aged between 16 and 21 years (63.9% females, M=18.7, SD=1.8). A 4 × 2 × 2 MANOVA was applied for the outcome variables of Internet addiction (loss of control, emotional need and dependence) and gambling (anticipation, desire, and relief) with parenting style (authoritative, authoritarian, indulgent, and neglectful), sex (boy vs. girls), and age (16-18 years old vs. 19-21 years old) as independent variables. The results provide evidence of the relationship between parenting styles and technological addictions, showing that parenting characterized by the use of practices of involvement and acceptance (authoritative and indulgent parenting) can act as protective factors for Internet addiction and online gambling addiction. On the contrary, authoritarian parenting, characterized by the use of strictness and imposition practices, would act as a risk factor for Internet addiction and online gambling addiction. The protective and risk effects of parenting styles over adolescents’ technological addictions take place irrespective of their sex and age.